Internalisasi Etos Kerja Siswa SMK melalui Budaya Kaizen: Studi Kualitatif di SMKN 1 Magelang - Ludfi Ayu Bela Insani; Novia Wahyu Wardhani (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to analyze the role of Kaizen-based school culture at SMKN 1 Magelang in shaping students' work ethic, particularly discipline, responsibility, thoroughness, and a mindset of continuous improvement, which has not been widely studied in previous research. Methods – This study uses a descriptive qualitative approach with semi-structured interviews and moderate participatory observation conducted from July to November 2025. Data was collected from one teacher and four students through purposive sampling, then analyzed using Miles and Huberman's interactive model with triangulation. Findings – The results show that student work ethic is not formed through separate programs but rather through Kaizen as a school culture system. Kaizen works through the habit of discipline and order (5S), teacher role modeling, and learning integration through Teaching Factory, Project-Based Learning, and industrial work practices, which continuously shape student work character. Research Implications – This study confirms Kaizen as a school culture system that contributes to the formation of vocational students' work ethic. Although limited to one school and a small number of informants, these findings offer a replicable framework for developing work ethics in vocational education.